PENGARUH RASIO KEUANGAN TERHADAP KINERJA BANK UMUM KONVENSIONAL PERIODE 2014-2019 - Mardin Mardin; A Ifayani Haanurat; Syafaruddin Syafaruddin (COMPETITIVENESS, 2021)
The purpose of this study was to test: 1) the influence of CAR on ROA in Conventional Commercial Banks, 2) the influence of LDR on ROA on Conventional Commercial Banks, 3) the influence of NIM on ROA in Conventional Commercial Banks. Data collection method using non participant observation method is by documenting all data required in this research as stated in the Indonesian Banking Statistics Report for the period of 2014 - 2019 which is available on the OJK website. The data analysis method in this study used multiple linear regression analysis to obtain a comprehensive picture of the influence between independent variables (CAR, LDR, NIM) and dependent variables (ROA) using the SPSS for Window program. The results showed the following: 1) Capital Adequacy Ratio (CAR) has a significant effect on variable Return on Asset (ROA) in conventional commercial banks indicated by a value of significance less than 0.05, so hypothesis 1 is accepted. 2) Loan To Deposit Ratio (LDR).has no significant effect on variable Return on Asset (ROA) in conventional commercial banks indicated by a value of significance greater than 0.05, so hypothesis 2 is rejected. 3) Net Interest Margin (NIM) has a significant effect on return on asset (ROA) variables in conventional commercial banks indicated by a significance value less than 0.05, so hypothesis 3 is accepted. 4) Net Interest Margin (NIM) is the variable that most dominantly affects Return on Asset (ROA)Keywords : CAR (Capital Adequacy Ratio), LDR (Loan To Deposit Ratio), NIM Net Interest Margin), ROA (Return on Asset)